Hepatitis B Vaccination and Infection Prevalence Among Men Who Have Sex With Men Who Travel Internationally. Issue 5 (May 2018) - Truong, Hong-Ha M.; Fatch, Robin; Do, Tri D.; McFarland, Willi
Abstract : Abstract: Among men who have sex with men traveling internationally, self-reported hepatitis B virus (HBV) vaccination prevalence was 77% and less prevalent among older men and those with HBV infection. The HBV infection prevalence was 25% and was associated with older age and HIV infection. Testing for chronic infection, universal vaccination, and treatment for populations with multiple risks is needed. Abstract : Hepatitis B virus vaccination coverage is still not universal among men who have sex with men. Vigorous testing for hepatitis B virus infection, universal vaccination, and treatment for populations with multiple risks for infection is needed.